Human bronchospheres - A mirror of bronchiolar surfaces? - Yiwen Yao; Richard F. Sprott; Felix Ritzmann; Alexander Grißmer; Frank Langer; Christian Herr; Carola Meier; Robert Bals; Christoph Beisswenger; Thomas Tschernig (Elsevier, 2022)
Background: For translational research on lung diseases it is desirable to have human organoids which resemble features of human tissue. Adult stem cells obtained from human bronchial epithelium can be differentiated to little tissue follicles, so-called bronchospheres. Aim of the study was to characterize structural details of bronchospheres treated with control media, lipopolysaccharide, and flagellin during the differentiation phase. Basic procedures: Human bronchial epithelial stem cells were prepared from surgical specimens and differentiated in Matrigel to bronchospheres. Histology and transmission electron microscopy revealed the cellular structure of the bronchospheres. Main findings: Follicles with a diameter of about 120 µm were confined by a bilayered epithelium with surface differentiation towards the inner lumen of the follicle and junctional complexes. Microvilli, kinocilia as well as secretory cells were found. Treatment with the bacterial flagellin resulted in the formation of secretory granules and inhibited the occurrence of kinocilia. Principal conclusions: Despite clear limitations such as lacking of smooth muscles and columnar epithelium human bronchospheres are an interesting tool for translational research. They can be useful for studies addressing developmental processes, infections, drug testing and toxicology.